Nutritional Assessment of Pre-School Children in Rural Villages of the Family Dynamics, Lifestyles and Nutrition Study (1997-2001) II. Prevalence of Undernutrition and Relationship to Household Socio-Economic Indicators - Leng, Chee Heng; Lin, Khor Geok; Arshad, Fatimah; Wan Muda, Wan Abdul Manan; Mohd Taib, Mohd Nasir; Safii, Nik Shanita; Karim, Norimah Abdul; Husin, Norlela Mohd; Hashim, Normah; Koon, Pob Bee; Yusof, Rokiab Mohd (Nutrition Society of Malaysia, 2002)
This paper describes the nutritional status of pre-school children and analyzes its relationship to various household socio-economic indicators. Padi, rubber and fishing villages from the Functional Groups Study (1992-1996) were selected for having a high prevalence of child undernutrition, and all children between the ages of 12 and 72 months were measured for their weights and heights in April-May 1998. The NCHS reference values were used to calculate z-scores, which were categorised according to WHO (1983) recommendations. Children between minus 2SD and minus 1SD of reference median were classified as mildly malnourished. Prevalence of underweight was higher (30.5%) than stunting (22.3%), while wasting was only 9.7%. Padi villages had the highest prevalence of undernutrition, followed by fishing, and then rubber villages. Mean household incomes were found to be significantly lower for children with worse nutritional status, and undernutrition was higher in households below the poverty line income. The odds ratios for having stunted children were significantly higher for households whose heads were agricultural own-account workers (OR 3.66, 95% CI = 1.37-9.79), agricultural waged workers (OR 2.75, 95% CI = 1.06-7.10), and non-agricultural manual workers (OR 2.49, 95% CI = 1.04-6.00) compared to non-manual workers. Various household socio-economic indicators showed significantly higher odds ratios for underweight, stunting and wasting. After adjusting for confounding effects by logistic regression analysis, however, only mother’s education was found to be a significant predictor for stunting, while poverty level and access to piped water supply were significant predictors for both underweight and stunting. Households without livestock were significant predictors for wasting. Thus, this study identified specific socio-economic factors that should be prioritized for policy and research towards the amelioration of childhood malnutrition in rural areas.